Arab Maghreb Union - Finaish, Mohamed (I.M.F. WashingtonUS, 1994)
Provides an overview of the economic conditions in the Arab Maghreb Union (AMU) member countries, describes the institutional arrangements under the AMU, and assesses the progress made in attaining the economic objectives of the Treaty. Identifies the main obstacles and renews action that needs to be taken to make further progress in the coming years. Examines the relationship of the AMU with the European Union.